Cross-Sectional Study: Psychosocial Factors and Blood Pressure Abnormalities Among Students of the Faculty of Economics and Business, UPN Veteran Jakarta - Sheren Aurellia; Maria, Ima; Desi Purwaningsih; Marlina Dewiastuti (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2026)
Background: Hypertension and prehypertension affect 10% and 14% of adolescents and young adults globally. Among university students, psychosocial stress, sleep disturbances, depression, anxiety, and caffeine consumption may synergistically trigger endothelial dysfunction and neurohumoral activation, serving as early predictors of hypertension. This study assessed the association between psychosocial factors (stress, anxiety, depression, sleep quality) and caffeine consumption with blood pressure among students of the Faculty of Economics and Business, UPN